Changing trends in the management of end-stage neuromuscular respiratory muscle failure: recommendations of an international consensus - Bach, John R. (2013)
OBJECTIVE: Respiratory management of patients with end-stage respiratory muscle failure of neuromuscular disease has evolved from no treatment and inevitable respiratory failure to the use of up to continuous noninvasive intermittent positive pressure ventilatory support (CNVS) to avert respiratory failure and to permit the extubation of "unweanable" patients without tracheostomy. An international panel experienced in CNVS was charged by the 69th Congress of the Mexican Society of Pulmonologists and Thoracic Surgeons to analyze changing respiratory management trends and to make recommendations. DESIGN: Neuromuscular disease respiratory consensuses and reviews were identified from PubMed. Individual respiratory interventions were identified; their importance was established by assessing the quality of evidence-based literature for each one and their patterns of use over time. The panel then determined the evidence-based strength for the efficacy of each intervention and made recommendations for achieving prolonged survival by CNVS. RESULTS: Fifty publications since 1993 were identified. Continuous positive airway pressure, oxygen therapy, bilevel positive airway pressure used at both low and high spans, "air stacking," manually assisted coughing, low pressure (<35 cm H2O) and high pressure (≥40 cm H2O) mechanically assisted coughing, noninvasive positive pressure ventilation part time (<23 hrs per day) and full time (>23 hrs per day; CNVS), extubation and decannulation of ventilator-dependent patients to CNVS, and oximetry feedback for noninvasive positive pressure ventilation and mechanically assisted coughing were identified. All noted interventions are being used with increasing frequency and were unanimously recommended to achieve prolonged survival by CNVS, with the exception of supplemental oxygen and continuous positive airway pressure, which are being used less and were not recommended for this population. CONCLUSIONS: CNVS and extubation of unweanable patients to CNVS are increasingly being used to prolong life while avoiding invasive interfaces.